Interrelation of economic confidence with other types of confidence - Бонецький, Орест Олегович (Technology audit and production reserves, 2013)
The paper gives the object and the subject of the study, which are used as a criterion allowing to separate the economic confidence from other types of confidence. The terms describing the psychological and sociological confidence are proposed. It was found that the economic confidence is interrelated with psychological confidence by motivation and advertising, sociological – by the results of activity of public organizations, state regulation of the economy. On the example of information-computer confidence (confidence in the system), the example of confidence in the banking system was considered and the result was obtained: in case the system does not justify the confidence, the principal has no confidence in the entire system (all system components, products, etc). The confidence is formed at the coincidence of basic values of participants of trust relationship. If there is no coincidence, the confidence will not be formed, and the acquired trust relations will become distrustful because of the change of behavior.